Correlation of Hepatitis C Antibody Levels in Gingival Crevicular Fluid and Saliva of Hepatitis C Seropositive Hemodialysis Patients - Gökhan Açıkgöz; Murat İnanç Cengiz; İlker Keskiner; Şereften Açıkgöz; Murat Can; Aydan Açıkgöz (Hindawi Limited, 2009)
Search for hepatitis C virus (HCV) in body fluids other than blood is important when assessing possible nonparenteral routes of viral transmission. However, the role of oral fluids in HCV transmission remains controversial. Our aim was to compare the prevalence of HCV antibody (HCV Ab) levels in saliva, and gingival crevicular fluid (GCF) of HCV seropositive hemodialysis patients. Serum, saliva and GCF samples were collected from thirty-nine patients. Samples were analyzed for HCV Ab using the Ortho HCV 3.0 SAVe enzyme-linked immunosorbent assay (ELISA). HCH Ab levels in saliva and GCF of all HCV-seropositive patients were statistically compared. Reported here are the results of the study designed to determine the correlation between HCV-RNA positivity in serum and the detection of antibodies in GCF and saliva. One hundred percent (100%) of the 39 patients have antibodies to HCV in their serum, 15.4% have antibodies to HCV in GCF, and saliva found out. HCV Ab seropositivity in GCF and saliva was significantly correlated (kappa = 0.462; 𝑃<.001). This study supports the concept that GCF may be a significant source of HCV in saliva.